Synthesis and Bactericidal Ability of TiO2 and Ag-TiO2 Prepared by Coprecipitation Method - Robert Liu; H. S. Wu; Ruth Yeh; C. Y. Lee; Yungtse Hung (International Journal of Photoenergy)
Preparation of photocatalysts of TiO2 and Ag-TiO2 was carried out by coprecipitation method. The prepared photocatalysts were characterized by X-ray diffraction (XRD), SEM, EDX, and XRF analysis. The disinfection of E. coli, a model indicator organism for the safe water supply, was investigated by using TiO2 and Ag-TiO2 under different light sources. The treatment efficacy for the inactivation of E. coli would be UV/Ag-TiO2; visible/Ag-TiO2; dark/Ag-TiO2; UV (all 100%) > UV/TiO2 (99%) > visible/TiO2 (96%) > dark/TiO2 (87%) > visible (23%) > dark (19%). The order of disinfection efficiency by their corresponding kinetic initial apparent rate constants, 𝑘app, (min−1) would be UV/Ag-TiO2; visible/Ag-TiO2 (both 6.67) > UV (6.6) > dark/Ag-TiO2 (6.56) > UV/TiO2 (1.62) > visible/TiO2 (1.08) > dark/TiO2 (0.7) > visible (0.28) > dark (0.03). The application of TiO2 doped with silver strongly improved the ability of disinfection treatment. The study of mineralization of E. coli by measurement of TOC (total organic carbon) removal percentage showed that the visible light may effectively be applied for the disinfection unit of water and wastewater treatment system by using photocatalysts of Ag-TiO2.